2007
DOI: 10.1007/s00384-007-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine vs continuous infusion 5-FU in neoadjuvant treatment of rectal cancer. A retrospective review

Abstract: CAP when compared to CIV seems to have superior efficacy with reasonable toxicities. It is reasonable to treat LARC with CAP + XRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
2
22
1
Order By: Relevance
“…Our results concerning tumor regression with a rate of 14% of complete regression (TRG4) correspond with the literature [16,25]. Additionally, we found a statistically significant correlation between high-grade acute organ toxicity during RCT and complete histopathologic tumor regression.…”
Section: Discussionsupporting
confidence: 79%
“…Our results concerning tumor regression with a rate of 14% of complete regression (TRG4) correspond with the literature [16,25]. Additionally, we found a statistically significant correlation between high-grade acute organ toxicity during RCT and complete histopathologic tumor regression.…”
Section: Discussionsupporting
confidence: 79%
“…In this analysis, we demonstrated that various cell types reach nadir at different time points and are influenced by different clinical and dosimetric predictors. To identify the myelosuppressive effect caused predominantly by RT, we investigated patients undergoing neoadjuvant CRT for rectal cancer, as 5-FU-based chemotherapy has been associated with lesser myelosuppressive properties [1214]. Acute hematologic toxicity associated with pelvic RT with continuous infusion 5-FU for rectal cancer has been reported up to 8% [5,1922], and pelvic RT with capecitabine was found to cause less HT in a randomized phase III trial comparing oral capecitabine and intravenous 5-FU chemotherapy (2% vs. 8% with Grade 3 neutropenia) [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assessed HT in locally advanced rectal cancer patients receiving pelvic RT with concurrent FU-based chemotherapy. Given that infusional 5-FU or capecitabine chemotherapy functioned mainly as a radiosensitizer in patients undergoing neoadjuvant CRT for rectal cancer and had been reported to be associated with a low rate of myelosuppression [12,1316], we felt that analyzing HT in this population would help us determine the myelosuppressive effect predominantly caused by pelvic RT. Our study aimed to establish the impact of standard long-course pelvic RT on BM suppression and to identify clinical and dosimetric predictors of HT.…”
mentioning
confidence: 99%
“…The most common acute responses were diarrhea, perineum skin radioactive reactions and the hematological toxicity. Capecitabine combined radiotherapy has the same security and toxicity response compared with 5-FU, with a relatively higher incidence of the hand-foot-syndrome [27,28] . Our study showed that preoperative chemoradiotherapy did not significantly increase the grade 3-4 toxicity, and most patients could tolerate the treatment, with a similar surgery mortality as most studies reported.…”
Section: Discussionmentioning
confidence: 93%